THE FUTURE OF PROGRAMMING: DEVELOPMENT TRENDS AND TRANSFORMATIONS IN THE NEXT FIVE YEARS - Qambarova Mohinur Sharof qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract:Programming has become one of the most essential skills in the digital era, serving as the foundation of modern technological innovation. Rapid advancements in Artificial Intelligence (AI), cloud computing, cybersecurity, quantum computing, and software engineering are reshaping the programming landscape. Over the next five years, programming is expected to undergo significant transformations driven by automation, low-code and no-code platforms, AI-assisted development tools, and emerging computing paradigms. This theoretical review examines the anticipated evolution of programming between 2026 and 2031 through an analysis of current technological trends and scholarly literature. The paper explores the opportunities and challenges that programmers, educational institutions, and technology industries may face in the near future. The findings suggest that while programming will become more accessible and efficient through intelligent automation, the demand for advanced problem-solving, creativity, and software architecture skills will continue to grow. The study concludes that programmers must adapt to changing technological environments through continuous learning and interdisciplinary competence.